La delincuencia en adolescentes y su relación con el consumo de drogas, en Hermosillo, Sonora - Valencia Arroyo, Arath Philip (Archivos de criminología, seguridad privada y criminalística, 2022)
This article aims to identify which drugs are consumed by adolescents who offend in the Mexican city of Hermosillo, Sonora and how these influence their criminal behavior, for this, a qualitative approach was used and the tool used for the methodology was the opinion interview, which was applied to 3 workers of the Specialized Prosecutor's Office for the Prosecution of Justice for Adolescents and Corruption of Minors of the State of Sonora, Mexico, which consisted of 10 questions previously structured to obtain relevant information for the research and to contrast the different answers given by the experts, who mainly agree that it is very common that adolescents who are arrested for any crime have a frequent use of drugs or are even arrested under the influence of these drugs.